HUKUM ZAKAT PERHIASAN EMAS DALAM PERSPEKTIF ISLAM (STUDI KOMPARASI ANTARA MAZHAB HANAFI DAN MAZHAB SYAFI’I) - Rosmita Rosmita; Kasman Bakry; Sri Reski Wahyuni Nur; Maryam Maryam; Yulianti Yusuf (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2024)
This study aims to determine the law of zakat on gold jewelry according to the ÃƒÂ¡Ã‚Â¸Ã‚Â¤anafÃƒâ€žÃ‚Â« and SyÃƒâ€žÃ‚Âfi'Ãƒâ€žÃ‚Â« schools as well as the similarities and differences between the two schools. To get answers to the above problems, the type of research used is qualitative research in the form of library research focused on manuscript and text studies. The research results found are; First, according to the ÃƒÂ¡Ã‚Â¸Ã‚Â¤anafÃƒâ€žÃ‚Â« school of thought, gold jewelry is obliged to pay zakat based on general and specific arguments regarding the law of gold zakat. Second, the Syafi'i School views that zakat on gold jewelery is not obligatory to pay. Third, the similarity of the views of the ÃƒÂ¡Ã‚Â¸Ã‚Â¤anafÃƒâ€žÃ‚Â« school and the SyÃƒâ€žÃ‚Âfi'Ãƒâ€žÃ‚Â« school regarding the law of zakat on gold jewelry is their agreement that it is obligatory to pay zakat on gold jewelry worn by men. The two schools of thought also agree that it is obligatory to pay zakat on gold jewelry that is forbidden to be used by women or men. The difference between the two schools of thought is their difference in looking at the gold jewelry, the Hanafi school views it in terms of the basic material of gold jewelry so that the law is the same as gold which is not used as jewelry that must be paid zakat while the SyÃƒâ€žÃ‚Âfi'Ãƒâ€žÃ‚Â« school views that gold jewelry has already been paid. is no longer judged as mining goods because it has changed its form so that it is the same as goods used to meet human needs so that zakat is not obligatory to be issued.